Globally Consistent Creditor Protection, Reallocation, and Productivity - Bo Bian (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2020)
This paper documents that resource reallocation across firms is an important mechanism through which creditor rights affect real outcomes. I exploit the staggered adoption of an international convention that provides globally consistent strong creditor protection for aircraft finance. After this reform, country-level productivity in the aviation sector increases by 12%, driven mostly by across-firm reallocation. Productive airlines borrow more, expand, and adopt new technology at the expense of unproductive ones. Such reallocation is facilitated by (i) easier and quicker asset redeployment; and (ii) the influx of foreign financiers offering innovative financial products to improve credit allocative efficiency. I further document an increase in competition and an improvement in the breadth and the quality of products available to consumers.
urn:nbn:de:hebis:30:3-616460
Keywords: D22; D24; G32; G33; K12; K33; L11; 330; Creditor Rights; Allocative Effciency; Reallocation; Productivity and Growth; Law and Finance